A 3‐D Printed PCB Integrated TEM Horn Antenna. Issue 1 (30th January 2019) - Miralles, Enrique; Schoenlinner, Bernhard; Belenguer, Ángel; Esteban, Héctor; Ziegler, Volker
Abstract: This paper presents a very broadband (5–40 GHz) novel three dimension (3‐D) printed Transverse ElectroMagnetic (TEM) horn antenna. It is integrated with a planar Printed Circuit Board and radiates in a perpendicular direction of the Printed Circuit Board. The described antenna provides benefits in terms of cost and size for a two dimensional antenna array. Here the antenna and its corresponding transition to a regular 50 Ω microstrip line through Parallel Plate Waveguide and a 90° bend are presented. Prototypes of back‐to‐back transitions and antenna are fabricated and measured. The antenna has a return loss below −10 dB and a gain of approximately 10 dBi over the targeted frequency range. Key Point: A novel transition from PCB to a 3‐D printed TEM horn antenna with a broadband (4 to 40 GHz) operational bandwidth is presented